2º Dia do Jovem Investigador do Instituto Nacional de Saúde Doutor Ricardo Jorge: livro de resumos - Instituto Nacional de Saúde Doutor Ricardo Jorge, IP (2017)
2º Dia do Jovem Investigador do Instituto Nacional de Saúde Doutor Ricardo Jorge, INSA, 8 maio 2017, Lisboa, Portugal